A cognitive-contextual framework of the marital conflict and children’s adjustment - Iraurgi, Ioseba; Martínez Pampliega, Ana; Iriarte, Leire; Sanz, Mireia (Anales de Psicología / Annals of Psychology, 2011)
The aim of these research is to check cognitive-contextual model’s validity in Spanish population as a theoretical framework which can explain the connection between marital conflict and childrens’ adjustment. 3957 students were included in the sample (50.2% female, 49.8% male; Average age= 15.68 years old). The following variables were assessed through questionnaires: children perception of interparental conflict (CPIC), children’s psychological well-being (YSR), academic performance (CDE) and family satisfaction (FS). Hierarchical regression models are able to explain the 22.6% of the variance on children’s emotional unrest, and the 26% on academic performance. A covariance structure model (CFI, GFI y AGFI >.95) has confirmed a clear and direct effect of interparental conflict on children’s affectivity, but no on academic performance, which is more directly affected by children’s emotional unrest. In other words, the relation between interparental conflict and academic performance is not direct, it is mediated by the level of affectivity.